Vicki Baum: Ausgewählte Werke. Kommentierte Ausgabe. Bd. 1: Die andern Tage. Novellen - Bertschik, Julia (Wallstein, 2025)
Vicki Baum's collection of novellas „Die andern Tage“ („The Other Days“), which the author endeavored to republish throughout her life, was published in 1922 and in a slightly different compilation in 1931. The eight novellas in both editions present the variety of themes, styles and genres from Baum's early work and her productions of the 1920s and 1930s, which continued to have an effect until her late work in exile in the USA. For the first time, this volume offers a reliable textual basis as well as an extensive contextualizing commentary section.